VaAPRT3 Gene is Associated With Sex Determination in Vitis amurensis - Men, Yan; Li, Ji-Rui; Shen, Hai-Lin; Yang, Yi-Ming; Fan, Shu-Tian; Li, Kun; Guo, Yin-Shan; Lin, Hong; Liu, Zhen-Dong; Guo, Xiu-Wu (Frontiers in Genetics, 2021)
In the past decade, progress has been made in sex determination mechanism in Vitis. However, genes responsible for sexual differentiation and its mechanism in V. amurensis still remain unknown. Here, we identify a sex determination candidate gene coding adenine phosphoribosyl transferase 3 (VaAPRT3) in V. amurensis. Cloning and sequencing of VaAPRT3 gene allowed us to develop a molecular marker able to discriminate female individuals from males or hermaphrodites based on a 22 bp InDel. Gene expression and endogenous cytokinin content analysis revealed that VaAPRT3 gene is involved in sex determination, or to be precise, in female organ differentiation, through regulating cytokinin metabolism in V. amurensis. This study enlarged the understanding of sex determination mechanism in the genus Vitis, and the sex marker could be used as a helpful tool for sexual identification in breeding programs as well as in investigation and collection of V. amurensis germplasms.